Urgensi Istinsyaq dalam Bahasa Hadist dan Medis - Mar’atussholikhah, Septiana; Amiruddin, Muhammad; Jadidah, Nur (Maliki Interdisciplinary Journal, 2025)
Istinsyaq, which is inserting water into the nose during ablution, is one of the recommended sunnah practices in Islam. In addition to having religious value, this practice also provides important health benefits. Research shows that istinsyaq helps clean the nasal cavity from dirt, dust, bacteria, and viruses that can interfere with the respiratory tract. In Islam, istinsyaq is supported by the hadiths of the Prophet Muhammad SAW, although it is not directly mentioned in the Qur'an. Some scholars, such as Imam Syafi'i and Imam Malik, consider istinsyaq as sunnah muakkadah (highly recommended sunnah) in ablution. Meanwhile, the Hambali school views it as an obligation based on the command of the Prophet SAW. From a medical perspective, istinsyaq is in line with the nasal irrigation technique used in the world of health to clean the respiratory tract. Studies show that istinsyaq can reduce the number of microorganisms in the nose, prevent respiratory tract infections, and reduce the risk of diseases such as sinusitis and allergies. However, despite its many benefits, the practice of istinsyaq faces various challenges in the modern era, such as low public awareness, negative views of traditional healing methods, and limited scientific research that proves its effectiveness. Efforts to overcome these challenges can be done through education and socialization regarding the benefits of istinsyaq, combining it with modern health practices, and increasing scientific research on its efficacy. With a deeper understanding, istinsyaq can be recognized not only as part of worship, but also as an effective way to prevent disease. Therefore, cooperation is needed between scholars, medical personnel, and academics to raise awareness of the role of istinsyaq in maintaining respiratory tract health.